Neural model of residential building air infiltration process - Malinowski, Pawel; Polarczyk, Iwona; Piotrowski, Jerzy (Journal of Civil Engineering and Management, 2006)
For the needs of this paper, certain area of issues associated with the infiltration process and neural networks were selected. In the scope of infiltration process, the measurements and analysis of air infiltration through the buildings have shown how difficult this process is in terms of strict mathematical models formulation. In the scope of neural networks, attention was given to multi‐layer perceptrons and systems composed of them. It must be noted that, due to the novelty of this method, a detailed description of the neuron network theory was presented in this paper as well as a thorough discussion of the neuron modelling process. The work was carried out in two stages, with the first stage covering the development of detailed methodology for the construction of neural model and the second stage in which a developed methodology was applied to modelling real objects.Neuroninis infiltracijos proceso gyvenamajame name modelisSantrauka. Šiam straipsniui pasirinkti aspektai, susiję su infiltracijos procesu ir neuroniniais tinklais. Infiltracijos pastatuose matavimai parodė, koks sudėtingas yra griežtas matematinis šio proceso modeliavimas. Analizuojant infiltracijos procesą neuroniniu tinklu požiūriu, dėmesys buvo skiriamas daugiasluoksniams perceptronams ir iš jų sudarytoms sistemoms. Atsižvelgiant į šio metodo naujumą, straipsnyje pateikiamas tiek neuronų tinklo teorijos, tiek išsamus neuroninio modeliavimo proceso aprašymas. Darbas buvo atliktas dviem etapais: pirmajame sukurta neuroninio modelio sudarymo metodika, antrajame ‐ši metodika buvo pritaikyta realiems objektams modeliuoti.Raktiniai žodžiai: infiltracijos procesas, neuroniniai tinklai, neuroniniai modeliai.First Published Online: 14 Oct 2010